The Relationship Between Knowledge And Husband Support With Completeness Of Tetanus Toxoid Immunization In Pregnant Women In The Working Area Of Puskesmas Lingkar Timur Bengkulu City In 2024 - Novelia, Novelia; Darmawansyah, Darmawansyah; Handayani, Tita Septi (Student Scientific Journal, 2025)
Intoduction: The coverage of Td2+ immunization for pregnant women in 2021 is 46.4%. This coverage is lower than the 2020 coverage of 54.7%, and also lower than the coverage of K4 pregnant women services which amounted to 88.8%. Meanwhile, Td2+ is a prerequisite for health services for K4 pregnant women. The purpose of this study was to determine the relationship between knowledge and husband support with the completeness of tetanus toxoid immunization in pregnant women in the Working Area of Puskesmas Lingkar Timur, Bengkulu City. Method: The design in this study used analytic observational with a cross sectional approach. Sampling using nonprobability sampling method with purposive sampling technique, respondents were 95 farmers in Bermani Ulu District. The statistical test in this study used the chi-square test bivariate analysis. Result and Discussion: The results of the univariate test analysis of most respondents (58.1%) with complete tetanus toxoid immunization, almost half of the respondents (38.7%) with sufficient knowledge, most respondents (61.3%) with supportive husband support. The results of bivariate analysis obtained the results of knowledge (0.000) and husband support (0.003) with the completeness of tetanus toxoid immunization in pregnant women. There is a relationship between knowledge and husband's support with the completeness of tetanus toxoid immunization in pregnant women. Conclusion: Researchers suggest that for Puskesmas the results of this study can be the basis for implementing a program of guidance, coaching, and counseling activities regarding tetanus toxoid immunization in pregnant women